2008
DOI: 10.5194/angeo-26-447-2008
|View full text |Cite
|
Sign up to set email alerts
|

New results on equatorial thermospheric winds and the midnight temperature maximum

Abstract: Abstract. Optical observations of thermospheric winds and temperatures determined with high resolution measurements of Doppler shifts and Doppler widths of the OI 630-nm equatorial nightglow emission have been made with improved accuracy at Arequipa, Peru (16.4 • S, 71.4 • W) with an imaging Fabry-Perot interferometer. An observing procedure previously used at Arecibo Observatory was applied to achieve increased spatial and temporal sampling of the thermospheric wind and temperature with the selection of eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 30 publications
11
87
1
Order By: Relevance
“…In the late winter to spring season of the Southern Hemisphere (e.g., the bottom panel of Fig. 7 of Meriwether et al, 2008), the wind is directed poleward during the early evening hours, followed by the equatorward surge immediately before midnight, and then it is reversed poleward again.. The periodic change in the wind direction is consistent with that represented in Fig.…”
Section: Origin Of the Wind Variationsupporting
confidence: 73%
See 1 more Smart Citation
“…In the late winter to spring season of the Southern Hemisphere (e.g., the bottom panel of Fig. 7 of Meriwether et al, 2008), the wind is directed poleward during the early evening hours, followed by the equatorward surge immediately before midnight, and then it is reversed poleward again.. The periodic change in the wind direction is consistent with that represented in Fig.…”
Section: Origin Of the Wind Variationsupporting
confidence: 73%
“…2 systematically varies through the night. Meriwether et al (2008) observed nightly variations of thermospheric winds and temperatures with high accuracy at a low-latitude station Arequipa, Peru (16.4 • S, 71.4 • W), which allowed to draw local time-latitude maps of horizontal wind. In the late winter to spring season of the Southern Hemisphere (e.g., the bottom panel of Fig.…”
Section: Origin Of the Wind Variationmentioning
confidence: 99%
“…The FPI uses the Doppler shift and Doppler width of the 6300 Å emission to determine these parameters (Meriwether et al, 2008).…”
Section: Instrumentation and Datamentioning
confidence: 99%
“…Another equatorial phenomenon we discuss in this paper, the MTM, has been studied directly using a variety of instruments such as satellites, incoherent scatter radars (ISR), and FPIs, (Herrero and Spencer, 1982;Hickey et al, 2014;Meriwether et al, 2008). At Jicamarca, the ISR has been used to study the seasonal dependence of the MTM (Bamgboye and McClure, 1982) and the MTM has been observed with FPIs at locations near the magnetic equator (Meriwether et al, 2008;Fisher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation